Non-invasive brain neuromodulation techniques for chronic low back pain - Tian-Tian Chang; Yu-Hao Chang; Shu-Hao Du; Pei-Jie Chen; Xue-Qiang Wang; Xue-Qiang Wang; Xue-Qiang Wang (Frontiers in Molecular Neuroscience, 2022)
Structural and functional changes of the brain occur in many chronic pain conditions, including chronic low back pain (CLBP), and these brain abnormalities can be reversed by effective treatment. Research on the clinical applications of non-invasive brain neuromodulation (NIBS) techniques for chronic pain is increasing. Unfortunately, little is known about the effectiveness of NIBS on CLBP, which limits its application in clinical pain management. Therefore, we summarized the effectiveness and limitations of NIBS techniques on CLBP management and described the effects and mechanisms of NIBS approaches on CLBP in this review. Overall, NIBS may be effective for the treatment of CLBP. And the analgesic mechanisms of NIBS for CLBP may involve the regulation of pain signal pathway, synaptic plasticity, neuroprotective effect, neuroinflammation modulation, and variations in cerebral blood flow and metabolism. Current NIBS studies for CLBP have limitations, such as small sample size, relative low quality of evidence, and lack of mechanistic studies. Further studies on the effect of NIBS are needed, especially randomized controlled trials with high quality and large sample size.